El Excentrico, 1960-01-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 20, 1960 [5 de enero de 1960]. Ano 10, No 10. Cover has a photograph of actress Maria Felix with headline "Noted actress Maria Felix to appear in San Jose Rainbow Ballroom."